Isolate or combined use of platelet-rich plasma in the treatment of temporomandibular joint osteoarthritis: a concise systematic review - Manna, Camila Alves (2023)
Introduction: In the context of temporomandibular disorders (TMD), temporomandibular joint osteoarthritis (TMJOA) is a common disease in the oral and maxillofacial regions, as well as being the most severe type. The incidence of TMD is high, affecting approximately 5%-12% of the population. There is evidence for the potential superiority of intra-articular platelet-rich plasma (PRP) injections in patients with TMJOA. Objective: This study aimed to carry out a systematic review to highlight the main clinical outcomes of the minimally invasive treatment of osteoarthritis of the temporomandibular joint through the injectable use of platelet-rich plasma. Methods: The research and development of the work were carried out from December 2022 to March 2023 in the Scopus, PubMed, Science Direct, and Scielo databases, using scientific articles from 2011 to 2022, following the PRISMA rules. The quality of the studies was based on the GRADE instrument and the risk of bias by the Cochrane instrument (Funnel Plot). Results and Conclusion: It was found 134 studies that underwent eligibility analysis. The final sample had 48 eligible studies and only 25 studies were described in the systematic review. Most studies showed homogeneity in their results, with X2 =91.2% >50%, with p<0.05. The symmetrical funnel plot did not suggest a risk of bias among studies with small sample sizes. Based on the objective of the present study, important clinical outcomes of the treatment of osteoarthritis of the temporomandibular joint were evidenced through the injectable use of platelet-rich plasma, alone or in combination with other types of treatment. However, it was observed that despite the extensive literature on the use of PRP in the treatment of joint disorders, its application in TMD is still largely unexplored.